“THE FEATURES OF PERCEPTION AND ANALYSING OF INFORMATION AS A REGULATORS OF PERSON’S BEHAVIOR IN SOCIAL NETWORKS” - Esoyan, V.A.; Hayrapetyan , D.R. (Modern Psychology, 2021)
In developing digital world the role of information flows are important for human existence. Human behavior and cognitive features are being adapted to the new environment of information, especially on social networks such as Facebook, Instagram, Twitter etc.... The main purpose of the research is to discover the significant connections between the styles of thinking and information processing and the behavior in the social networks. Main target of the research are young Armenian representatives of age 18 to 30. For the study we applied the questionnaire that discovered the behavior in social networks such as Facebook, Instagram and Twitter; Harrison A.F., Brainson R.M. “Thinking styles” questionnaire. The outcome of the research shows that information selection and concentrating on the certain content is due to a certain style of thinking and information processing.
Keywords: Information processing, Styles of thinking, Information flows, Social networks, Perception, behavior.